Adaptation of the Canadian indigenous cognitive assessment in three provinces and evidence for validity: Development and validation of cognitive and quality of life assessments for older indigenous peoples internationally. (7th December 2020) - Walker, Jennifer D; O'Connell, Megan E; Crowshoe, Lynden; Jacklin, Kristen; Boehme, Gail; Hogan, David B; Pitawanakwat, Karen; Blind, Melissa J; Warry, Wayne; Akan, Nicole; Patterson, Christopher; Allaby, Cheryl
Abstract: Background: The Canadian Indigenous Cognitive Assessment (CICA) tool is an innovative culturally‐grounded dementia case finding tool. Currently, dementia is underdiagnosed and when diagnosis occurs it is at later stages in Indigenous populations in Canada when compared to the general population; a trend documented in Indigenous populations beyond Canada, including Australia and New Zealand. As communities and health systems prepare for rapidly aging Indigenous populations with high rates of multiple chronic conditions, the need for an accurate, reliable dementia case‐finding tool in Canada is critically needed to inform necessary supports and services. Method: An interdisciplinary, international team composed of researchers and Indigenous community partners led the development of the CICA. The CICA is a community‐based adaptation of the Kimberley Indigenous Cognitive Assessment (KICA) tool, which is a validated dementia screening assessment that was originally developed with Indigenous populations in Western Australia. To adapt the KICA for Canadian contexts, we undertook iterative and community‐specific processes of translation, adaptation, and piloting before we conducted reliability and validity testing in three different sites: Manitoulin Island, Ontario, which is home to seven First Nations communities; an urban Indigenous population in Calgary, Alberta; and File Hills Qu'Appelle Tribal Council, Saskatchewan, which serves 11 First Nations communities. The adaptation process was community‐driven in each site and integrated both Indigenous community knowledge and trauma‐informed approaches to cognitive assessment. The intersections of culture, geography and colonial trauma were explored across these diverse Indigenous communities. Result: The resulting CICA adaptations were scored out of a possible 39 points and took approximately 15 minutes to administer. The CICA assessed 11 domains of cognition including orientation, recognition and naming, registration, verbal comprehension, verbal fluency, recall, visual naming frontal/executive functioning, free recall, cued recall, and praxis using culturally safe methods in English, Anishinaabemowin, and Nakota. For successful adaptation from the KICA, the orientation, verbal comprehension, verbal fluency, praxis, and naming domains required the most adaptation. Preliminary results indicate that the CICA demonstrated strong inter‐rater reliability, test‐retest reliability, and criterion validity. Conclusion: The CICA is the first tool of its kind in Canada and offers promising applications in the detection of dementia among Indigenous populations.